Site‐directed mutagenesis of HLA molecules reveals the functional epitope of a human HLA‐A1/A36‐specific monoclonal antibody. (25th November 2022) - Meng, Tina; Bezstarosti, Suzanne; Singh, Ujjwala; Yap, Michelle; Scott, Laura; Petrosyan, Naiiry; Quiroz, Fred; Eps, Ned Van; Hui, Eric Ka‐Wai; Suh, David; Zhu, Quansheng; Pei, Rui; et al.
Abstract : Eplet 44KM is currently listed in the HLA Epitope Registry but does not adhere to the eplet definition of an amino acid configuration within a 3.5 Å radius. Eplet 44KM has been previously redefined to the antibody‐verified reactivity pattern 44K/150V/158V, based on reactivity analysis of monoclonal antibody VDK1D12. Since the three residues are always simultaneously present on common HLA alleles, methods to define which residue is crucial for antibody‐induction and binding are limited. In this proof‐of‐concept study, we performed site‐directed mutagenesis to narrow down the antibody‐verified reactivity pattern 44K/150V/158V to a single amino acid and defined 44K as the eplet or functional epitope of mAb VDK1D12.